EL DESARROLLO DE HABILIDADES PARA EL TRABAJO CON MAGNITUDES DESDE LA CONCEPCIÓN VIGOTSKIANA: THE DEVELOPMENT OF SKILLS FOR WORKING WITH MAGNITUDES FROM A VYGOTSKY´S CONCEPTION - Fernández Chelala, Rosa María; Díaz Carbonell, Niliam (Opuntia Brava, 2018)
En el artículo se hace un análisis de los principales sustentos del enfoque histórico cultural de Vigotsky que fundamentan el desarrollo de las habilidades del trabajo con magnitudes, y se proponen ejercicios para su aplicación, los que contribuyen a la preparación del alumno para la vida: desarrollar todas sus potencialidades tanto para resolver las situaciones cotidianas como para enfrentarse a nuevas situaciones, que desde una concepción vigotskiana se traduce en tener presente lo que sabe, lo que puede hacer con ayuda o por sí solo. ABSTRACT It is an aspiration of our society to educate citizens prepared to participate actively in the satisfaction of his own needs, making use of the advances of science and technology; that imposes the school the duty to perfect the student’s education for life, and it implies to develop in the students all the potentialities, not only to solve daily life situations, but also to face new ones, that, from the Vygotsky’s conception of learning, is translated to the different aspects that take into account what the student knows, what he can do by himself or with certain levels of help. The present article analyzes the fundamental foundations of Vygotsky’s historical-cultural approach that sustains the ability development when working with magnitudes and some exercises are proposed for its application. KEY WORDS: Activity, abilities, magnitudes, Vygotsky’s conception